Persepsi Peserta Pelatihan Satuan Pengamanan Gada Pratama Terhadap Pelaksanaan Program Di PT Wiratama Jaya Perkasa - Heru Mardiansa; Vevi Sunarti (Universitas Negeri Padang, 2022)
This research was motivated by the good implementation of the Gada Pratama security unit training program at PT Wiratama Jaya Perkasa. The purposes of this study were 1) to see the participants' perceptions of the opening of the implementation of education and training, 2) to see the participants' perceptions of the education and training learning activities, 3) to see the participants' perceptions of the closing activities of the education and training implementation process.The type of research used is descriptive, with a quantitative approach. The population of this study were trainees from batches 45 to 50. While the samples were taken using the cluster random sampling technique. Data collection techniques using a questionnaire. As for the data analysis technique used the percentage formula.The results of this study indicate that the perception of participants in the Gada Pratama security unit training at PT Wiratama Jaya Perkasa is very good. It is shown that: 1) participants' perceptions of the opening of the implementation of education and training at PT Wiratama Jaya Perkasa are categorized as good. This is proven that in the implementation of the opening the instructor is able to influence the participants who take part in the training process; 2) participants' perceptions of learning and training activities at PT Wiratama Jaya Perkasa are categorized as good. It is proven that the instructor is able to carry out learning activities well so that participants are able to receive the material or training provided; 3) participants' perceptions of the closing activities of the education and training implementation process carried out at PT Wiratama Jaya Perkasa were categorized as good. It is proven that the closing activities carried out by the instructor have an influence on the participants who take part in the training